2023
DOI: 10.3389/fvets.2023.1050510
|View full text |Cite
|
Sign up to set email alerts
|

Social behaviors as welfare indicators in teleost fish

Abstract: Animal welfare is a key issue not only for aquaculture industry and food production, but also for daily husbandry practices in research topics related to physiology in wild and farmed animals. In this context, teleost fish constitute interesting models to assess alternative welfare indicators because of their wide diversity in reproductive and social structures. Any framework for assessing teleost fish welfare needs to account for the physiological mechanisms involved in each species as a first step. A compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 143 publications
0
3
0
Order By: Relevance
“…), selective breeding has been employed to enhance the social behavior and compatibility of individuals within a group [28]. Studies have shown that certain genetic factors contribute to the development of harmonious social structures that reduce aggression and stress in captive environments [29]. Advancements in molecular genetics have provided a more precise understanding of the genetic basis of ornamental traits.…”
Section: Selective Breeding For Desirable Traitsmentioning
confidence: 99%
“…), selective breeding has been employed to enhance the social behavior and compatibility of individuals within a group [28]. Studies have shown that certain genetic factors contribute to the development of harmonious social structures that reduce aggression and stress in captive environments [29]. Advancements in molecular genetics have provided a more precise understanding of the genetic basis of ornamental traits.…”
Section: Selective Breeding For Desirable Traitsmentioning
confidence: 99%
“…The behavioral-based indicators are those traits that are used to visually observe and identify abnormal or maladaptive/sterotypic behaviors of a fish. These behaviors include submissive or aggressive activities, changes in food intake or foraging activities, and changes in schooling or shoaling activities [ 76 , 77 ]. Unfortunately, the majority of species of fish that are maintained in aquarium and zoological settings have never had a thorough documentation of their natural behaviors, and as a result the recognition of subtle abnormal or maladaptive behaviors becomes challenging and generally extrapolated from other species [ 78 ].…”
Section: Welfare Assessmentmentioning
confidence: 99%
“…Several groups of neurohormones are involved in mediating social and reproductive behavior via interactions with other neuropeptides or neurotransmitter systems in the fish brain, including alternative phenotypes (variation in social dominance or the control of a territory) and/or social cognition (interactions) [19][20][21][22][23]. Among these neuropeptides, the vasopressin-vasotocin peptide family modulates several processes in reproductive physiology, comprising both aggressive and reproductive behaviors [19,24,25].…”
Section: Introductionmentioning
confidence: 99%